O conceito de indagação dialógica em Gordon Wells: indicações para o ensino nas salas de aula contemporâneas - Souza, Michelle de (Universidade Federal de São Carlos, 2024)
This work is the result of a bibliographic research conducted through content analysis of the book “Indagación dialógica: hacia una teoría y una práctica socioculturales de la educación”, written by Gordon Wells and originally published in 1999. Its aim was to analyze how the concept of dialogic inquiry can contribute to the improvement of teaching and learning processes in contemporary classrooms. The specific goal was to identify and extract from this author's work key indications for transforming teaching practice in the classroom. The guiding questions for this research are as follows: What is the role of the teaching profession in the concept of dialogic inquiry? How can this concept contribute to transforming teaching practice for teaching and learning in the information society? The methodological approach adopted is based on the guidelines of Bardin (2015), involving a careful analysis of the selected material, the separation of analytical categories, the formulation of hypotheses, and the treatment of the results found. The theoretical framework selected engages with the author's concept and is grounded in the communicative conception of education, which sees dialogicity as the means through which we can reduce educational inequalities. As results, we found that dialogic inquiry is relevant in the information society, as it contributes to overcoming the traditional teaching model, altering the rules that prescribe the actions of educators, and addressing the challenge of producing knowledge in this society. The analysis concluded that dialogic inquiry is not just a concept, but a way of being that has a high transformative potential for teaching practice and aligns with a teaching approach that enables students to understand how knowledge is co-constructed.
The concept of dialogic inquiry in Gordon Wells: implications for teaching in contemporary classrooms
El concepto de indagación dialógica en Gordon Wells: indicaciones para la enseñanza en las aulas contemporáneas
Keywords: Discurso em sala de aula; Ensino e aprendizagem; Conhecimento; Prática docente; Gordon Wells; Classroom discourse; Teaching and learning; Knowledge; Teaching practice; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM